The Transcription Factor bHLH121 Interacts with bHLH105 (ILR3) and Its Closest Homologs to Regulate Iron Homeostasis in Arabidopsis. Issue 2 (27th November 2019) - Gao, Fei; Robe, Kevin; Bettembourg, Mathilde; Navarro, Nathalia; Rofidal, Valérie; Santoni, Véronique; Gaymard, Frédéric; Vignols, Florence; Roschzttardtz, Hannetz; Izquierdo, Esther; Dubos, Christian
Abstract : bHLH121 acts upstream of the iron homeostasis regulatory network and directly regulates the expression of the large majority of genes encoding proteins and peptides involved in this regulatory cascade. Abstract: Iron (Fe) is an essential micronutrient for plant growth and development. Any defects in the maintenance of Fe homeostasis will alter plant productivity and the quality of their derived products. In Arabidopsis ( Arabidopsis thaliana ), the transcription factor ILR3 plays a central role in controlling Fe homeostasis. In this study, we identified bHLH121 as an ILR3-interacting transcription factor. Interaction studies showed that bHLH121 also interacts with the three closest homologs of ILR3 (i.e., basic-helix-loop-helix 34 [bHLH34], bHLH104, and bHLH115). bhlh121 loss-of-function mutants displayed severe defects in Fe homeostasis that could be reverted by exogenous Fe supply. bHLH121 acts as a direct transcriptional activator of key genes involved in the Fe regulatory network, including bHLH38, bHLH39, bHLH100, bHLH101, POPEYE, BRUTUS, and BRUTUS LIKE1, as well as IRONMAN1 and IRONMAN2 . In addition, bHLH121 is necessary for activating the expression of transcription factor gene FIT in response to Fe deficiency via an indirect mechanism. bHLH121 is expressed throughout the plant body, and its expression is not affected by Fe availability. By contrast, Fe availability affects the cellular localization of bHLH121 protein in roots. Altogether, these data show that bHLH121 is a regulator of Fe homeostasis that acts upstream of FIT in concert with ILR3 and its closest homologs.